Growth and enduring epidemic diseases - Bell, Clive; Gersbach, Hans (Journal of economic dynamics & control, 2013)
This paper analyzes the interplay of human capital formation and economic growth when there is premature adult mortality. Failing adequate insurance arrangements, a long wave of such mortality can so undermine human capital formation as to induce an economic collapse. In nuclear family structures, random matching of partners is superior to assortative mating only if the shock is not too big and initial levels of human capital are not too low. Full pooling of mortality risks with equal treatment of all children in extended families may fend off a general collapse, depending on the initial conditions and the size and duration of the shock. To avoid undesirable effects on expectations, awareness campaigns should be complemented by policies that credibly promise to reduce future mortality. If mortality depends on the general level of human capital, indeterminacy can arise in the form of more than one rational expectations path.
Gesehen am 01.12.2020